Meningkatkan Pemahaman Siswa Terhadap Kandungan Ayat-Ayat Keragaman Di Kelas IV SD Negeri 07 Padang Sarai - Syafitri, Oliza (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This Classroom Action Research (CAR) aims to improve students' learning outcomes in Islamic Religious Education (PAI) through the implementation of the Card Sort method at SDN 02 Maringging. The problem addressed is the low student achievement due to the lack of variety in teaching methods. The research was conducted in two cycles, each consisting of planning, implementation, observation, and reflection phases. The results show a significant improvement in students' learning outcomes. The percentage of learning mastery increased from 25% in the pre-test to 41.66% in cycle I, and 83.33% in cycle II. The students' average scores also improved, and they became more active and engaged in the learning process. Thus, the implementation of the Card Sort method effectively enhances PAI learning outcomes and can serve as an alternative teaching method in elementary schools.